Non‐indicated acid‐suppression prescribing in a tertiary paediatric hospital: An audit and costing study. (28th November 2018) - Riess, Suzi; Lei, Shaoke; Huang, Li; O'Loughlin, Rachel; Hiscock, Harriet
Abstract : Aim: To quantify (i) indicated versus non‐indicated prescribing of acid‐suppression therapies (AST) in a tertiary paediatric hospital; (ii) patient, provider and hospital factors associated with non‐indicated prescribing; and (iii) medication costs. Methods: This was a prospective, electronic medical audit conducted at The Royal Children's Hospital (RCH) Melbourne in August–September 2016. Proton pump inhibitor (PPI) and histamine‐2 receptor antagonist (H2 RA) prescriptions were extracted, with relevant patient, provider and hospital data. Logistic regression analysis of variables associated with indicated and non‐indicated prescribing was undertaken. Costs of indicated and non‐indicated prescriptions were estimated, with annual costs projected. Results: There was more non‐indicated than indicated prescribing across inpatient, outpatient and emergency department settings. Of the total 303 prescriptions analysed, 238 (78.5%) were non‐indicated. Gastrostomy presence (odds ratio (OR) 5.51 (1.96–15.46), P = 0.001), consultant providers (OR 2.69 (1.23–5.87), P = 0.01) and inpatient setting (OR 2.35 (1.16–4.77), P = 0.02) were all associated with a higher likelihood of non‐indicated prescribing. The child having a predisposing diagnosis was significantly associated with indicated prescribing (OR 0.41 (0.21–0.80), P = 0.009). A total of 75% of hospital and patient spending was for non‐indicated prescriptions. Annual costs of non‐indicated AST for Melbourne's RCH were projected to be $15 493. Conclusions: Non‐indicated acid‐suppression prescribing is common in a tertiary paediatric hospital and associated with gastrostomy presence, consultant providers and inpatient status. Future research should use qualitative methods to understand clinician and patient drivers of prescribing and use this information to develop and test targeted solutions to reduce non‐indicated AST prescribing.